2019
DOI: 10.1089/neu.2018.6127
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Closed Head Injury Models of Mild Traumatic Brain Injury in Mice and Rats

Abstract: Mild TBI (mTBI) is a significant health concern. Animal models of mTBI are essential for understanding mechanisms, and pathological outcomes, as well as to test therapeutic interventions. A variety of closed head models of mTBI that incorporate different aspects (i.e., biomechanics) of the mTBI have been reported. The aim of the current review was to compile a comprehensive list of the closed head mTBI rodent models, along with the common data elements, and outcomes, with the goal to summarize the current stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 427 publications
0
88
0
Order By: Relevance
“…This model offers multiple advantages, which include the capacity to titrate the intensity of impact, depth of injury and duration of impact. Most critically, it does not involve craniotomy, thereby facilitating multiple mild injuries and reducing infectious complications [5].…”
Section: Repetitive Mild Traumatic Brain Injury (Rmtbi) Plus Stress Smentioning
confidence: 99%
“…This model offers multiple advantages, which include the capacity to titrate the intensity of impact, depth of injury and duration of impact. Most critically, it does not involve craniotomy, thereby facilitating multiple mild injuries and reducing infectious complications [5].…”
Section: Repetitive Mild Traumatic Brain Injury (Rmtbi) Plus Stress Smentioning
confidence: 99%
“…Acoustic startle frequently measures the Vmax of the startle response. Previous studies by others showed acoustic startle response was inhibited in a variety of different TBI models (Sackheim et al, 2017;Teutsch et al, 2018;Bodnar et al, 2019). Therefore, the frequency of trials that had a Vmax of zero was assessed.…”
Section: Acoustic Startle Responsementioning
confidence: 99%
“…However, studying the chronic effects of mTBI is challenged by the lack of a suitable rodent model with prolonged symptoms similar to those in patients with mTBI. In most mTBI rodent models, the majority of behavioral abnormalities recover spontaneously within 3-4 weeks or have not been assessed for longer than that period (28)(29)(30)(31)(32). To establish an animal model of mTBI with neurobehavioral abnormalities that can last for months, we used repetitive mild closed head impacts to induce the brain injury in mice.…”
Section: Introductionmentioning
confidence: 99%